40 x 40. (San Gimignano : Galleria Continua, 1994)
Balducci, Franco ; Bettoni, Marco ; Biagi, Massimo ; Bonechi, Lorenzo ; Catelani, Antonio ; Corsini, Vittorio ; Corti, Stefano ; Craige, Sheppard ; De Leonardis, Federico ; De Lorenzo, Daniela ; De Zan, Guido ; Dobara, Satoshi ; Hidding, Martin ; Fabiani, Paolo ; Fontanelli, Lorenzo ; Fusi, Federico ; Gherardi, Isabella ; Giannetti, Emanuele ; Giampaia, Sauro ; Guaita, Carlo ; Gualdi, Guido ; Ionda, Franco ; Lillo, Giovanni ; Pinto, Antonio Lo ; Macca, Claudio ; Manetti, Mauro ; Nido, Davide ; Pancrazzi, Luca ; Parisi, Paolo ; Perego, Daniela ; Ponciano, Flores ; Ristori, Sandro ; Porta, Pedro Riz A ; Sabato, Sabrina ; Santarlasci, Andrea ; Secci, Alessandro ; Sedmach, Manuela ; Roma, Serse ; Sgherri, Gianluca ; Ziemacki, Giuseppe
40 x 40, Galleria Continua, San Gimignano, 1994
Italiaans
kunstcatalogus